Juicio moral de la conducta agresiva en competencia: un análisis en futbolistas universitarios (2021)
The purpose of this study was to examine the acceptability of aggressive response in competition in a group of 192 university soccer players in Bogotá (men = 141 and women = 51) from the Information Integration Theory. A questionnaire with 24 scenarios was designed and applied combining the variables: importance of the game, previous aggression, and type of aggressive response. The results show the differences with respect to moral judgment of this behavior in four clusters from a k-means analysis and ANOVA. Differences were identified according to gender (T = 3.37, p < 0.002) and positions on the playing field (F = 2.83, p <0.05; ƞ²ρ = 0.44); however, the importance of the disputed game was not found to be context for the acceptability of aggression in any cluster. Finally, we discuss possible explanations of the failure of algebraic laws for the study of moral judgment in this research and make suggestions for improving studies on moral judgment in sports.